India’s meat export: Structure, composition and future prospects - A, Suresh; Kavita, B; Chaudhary, K R (The Indian Journal of Animal Sciences, 2012)
The study analyses the structure of India’s meat export, the commodity and market diversification and the prospects of ushering the meat export. The domestic meat production increased from 2.6 million tonnes in 1980 to 6.3 million tonnes in 2010, fuelled by the growth in poultry and buffalo meat production. While buffalo meat accounts for about 23% total production, its contribution in meat export accounts for more than 85%, mostly in frozen form. The growth of meat export has slowed down in the last decade compared to the previous decade with increased instability. Indian meat export has been increasingly getting specialized towards buffalo meat whereas its export markets are gradually getting diversified. Cashing in the competitiveness of India’s buffalo, pig and small ruminant production and improving the competitiveness of poultry meat production would help to improve its export performance. Greater investment in disease control and safe meat production so as to adhere with the Sanitary and Phyto- Sanitary Measures of WTO would help in sustainable meat export.